Strategies to Improve Brand Awareness through Digital Marketing on Instagram to Boost Sales of Tikacollectionid Fashion Products - Kartikajati, Fauzana; Sunarta, Sunarta; Sarji, Sarji (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The development of information technology today is encouraging various significant changes in human life, including in the world of business and business. Design/methodology/approach: Used a qualitative research method with a descriptive approach. Qualitative research is intended to understand phenomena related to what is experienced by research subjects, such as behavior, perceptions, motivations, and actions in a holistic manner. Findings: Buying and selling transactions that used to be conventional with physical stores and a face to face system have now changed to digital or online based with a screen to face system. More and more businesses are providing products and services online without having to have a physical shop like conventional businesses in general. An online-based shop, also known as an online shop, is a business where consumers can buy products or services through an internet-based application or platform, without having to come to the shop and transact directly with the seller. However, online product and service transactions, especially online shops on social media (not via marketplace platforms) require the establishment of mutual trust between buyers and sellers. This condition is a challenge for online shops to be able to create a good brand image in order to gain the trust of consumers, thereby creating brand awareness. Therefore, in an effort to increase product sales, brand awareness is needed from consumers, so that business people can respond to market needs according to current developments and continue to survive in the midst of increasingly competitive business competition. Paper type: Research Paper